The Effect of PGPR bacteria on the response of some biochemical and qualitative characteristics of maize plants under the influence of water stress - ناصيف احمد; ياسر حماد; جهاد ابراهيم; مجد درويش (Latakia University Journal -Biological Sciences Series, 2024)
This study was conducted with the aim of reducing the effect of water stress on maize plants by using several types of PGPR bacteria distributed in two groups in the form of two types of biofertilizers to determine the effectiveness of each group individually and the effectiveness of mixing them in resisting water stress at three levels of water stress (1200,800,400) millibars. The research was carried out in the village of Al-Hanadi in Latakia City during the 2021-2022 season by planting yellow corn (Ghouta 82) in experimental plots according to a randomized complete block design (RCBD). Inoculation with PGPR bacteria led to positive effects on some biochemical properties (leaf content of NPK%, leaf content of proline µg/g, leaf content of salicylic acid µg/g, leaf content of total soluble sugars%) and quality (grain content of NPK%, grain content of protein%) in yellow maize plants growing under natural conditions and under stress conditions as well. Water stress at the levels of 1200 and 800 mbar (Ѱ2 and Ѱ3) result a decrease in the content of yellow maize grains of total protein and of nitrogen, phosphorus and potassium. PGPR bacteria contributed to increasing proline, salicylic acid, and total soluble sugars, thus increasing the stimulation of systemic resistance in the yellow maize plant (Ghouta 82). Accordingly, inoculation with PGPR bacteria can be suggested for its tangible role in the plant’s tolerance to water stress, as well as its role in stimulating growth through Providing nitrogen, phosphorus and potassium in the soil.